Regarding the Problem of Defining the Concept of «Administrative and Legal Provision of Citizens’ Rights» - Іванова, Ганна Сергіївна; Іванова, Г. С.; Иванова, Анна Сергеевна; Ivanova, Hanna S.; Фелик, Василь Іванович; Фелик, В. І.; Фелик, Василий Иванович; Felyk, Vasyl I.; Шопіна, Ірина Миколаївна; Шопіна, І. М.; Shopina, Iryna M.; Бєляков, Костянтин Іванович; et al. (Universidad de la Amazonia, 2020)
The purpose authors of this article aim to analyze the scientific literature on understanding the concept of “administrative and legal provision of civil rights”, its structural components and on this basis to offer our own view in regard to this administrative and legal category. To achieve this goal, such methods of scientific knowledge were used as: formal-logical; comparative analysis; logical and legal. Different scientific approaches and concepts to defining the notion of citizens’ rights have been analyzed in the article. On this basis the understanding of the category of “administrative and legal provision of citizens’ rights” has been improved. It includes two interrelated components – “administrative and legal” and “provision”. It has been determined that the term provision in the general sense means the creation of conditions, security, protection of something from danger. The rights of citizens as a subject matter of administrative provision have been analyzed. The features of human and civil rights have been outlined. It has been stated that human and civil rights, freedoms and legitimate interests in the modern world must be both declared in regulatory acts, and must be really guaranteed and secured by the state. It has been emphasized that officials of the state authorities, including law enforcement system, play a crucial role in the development of interaction between society, government and citizens. The main directions of ensuring the rights, freedoms and legitimate interests of citizens by the norms of administrative legislation, as well as the mechanism of their implementation have been determined. The authors have offered own definition of the concept of “administrative and legal provision of citizens’ rights”.

Мета статті – здійснити аналіз наукової літератури на предмет тлумачення поняття «адміністративно-правове забезпечення прав громадян», його структурних складових, на основі чого запропонувати власне бачення даної адміністративно-правової категорії. З метою досягнення поставленої мети використані такі методи наукового пізнання, як: формально-логічний; порівняльного аналізу; логіко-правовий. У статті проаналізовані різні наукові підходи та концепції до визначення поняття прав громадян, на підставі чого вдосконалено тлумачення категорії «адміністративно-правове забезпечення права громадян», що включає в себе дві взаємопов’язані складові —«адміністративно-правове» та «забезпечення». Визначено, що термін забезпечення у загальному змісті означає створення умов, охорону, захист чого-небудь від небезпеки. Проаналізовано права громадянина, як предмет адміністративного забезпечення. Окреслено ознаки прав людини і громадянина. Констатовано, що в сучасному світі права, свободи та законні інтереси людини та громадянина повинні бути не тільки задекларовані у нормативно-правових актах, але й реально гарантуватися й забезпечуватися державою. Наголошено, що саме посадові особи органів державної влади, в тому числі правоохоронної системи, відіграють вирішальну роль в розвитку взаємодії суспільства, влади та громадян. Визначено основні напрямки забезпечення нормами адміністративного законодавства прав, свобод і законних інтересів громадян, а також механізму їх реалізації. Запропоновано авторське визначення поняття «адміністративно-правове забезпечення прав громадян».

Цель статьи - осуществить анализ научной литературы на предмет толкования понятия «административно-правовое обеспечение прав граждан», его структурных составляющих, на основе чего предложить собственное видение данной административно-правовой категории. Для достижения поставленной цели использованы такие методы научного познания, как: формально-логический; сравнительного анализа; логико-правовой. В статье проанализированы различные научные подходы и концепции к определению понятия прав граждан, на основании чего усовершенствовано толкование категории «административно-правовое обеспечение права граждан», включающей в себя две взаимосвязанные составляющие - «административно-правовое» и «обеспечение». Определено, что термин обеспечение в общем смысле означает создание условий, охрану, защиту чего-либо от опасности. Проанализированы права гражданина, как предмет административного обеспечения. Определены признаки прав человека и гражданина. Констатировано, что в современном мире права, свободы и законные интересы человека и гражданина должны быть не только задекларированные в нормативно-правовых актах, но и реально гарантироваться и обеспечиваться государством. Отмечено, что именно должностные лица органов государственной власти, в том числе правоохранительной системы, играют решающую роль в развитии взаимодействия общества, власти и граждан. Определены основные направления обеспечения нормами административного законодательства прав, свобод и законных интересов граждан, а также механизма их реализации. Предложено авторское определение понятия «административно-правовое обеспечение прав граждан».
Ivanova H. Regarding the Problem of Defining the Concept of «Administrative and Legal Provision of Citizens’ Rights» / H. Ivanova, V. Felyk, I. Shopina, K. Bieliakov // Amazonia Investiga. – V. 9(26). – Universidad de la Amazonia, 2020. – P. 473-478.
Keywords: rights of citizens; administrative and legal mechanism; provision; administrative and legal provision; права громадян; адміністративно-правовий механізм; забезпечення; адміністративно-правове забезпечення; права граждан; административно-правовой механизм; обеспечение; административно-правовое обеспечение; Research Subject Categories::LAW/JURISPRUDENCE